IMPLEMENTING INVENTORY MANAGEMENT SYSTEM AT TOKO SINAR PRATAMA - Sutini Sutini; Wisnu Yuwono (Universitas Internasional Batam, 2022)
Sinar Pratama Store is an MSME located in Tanjung Uban that sells bicycles, motorcycle equipment, lawn machines, etc. The issue that Sinar Pratama Store has is the shop owner's difficulty in checking inventory. From the start of business, store supplies have only been recorded manually in books and notes. Therefore, this community service activity aims to design an inventory recording system at Sinar Pratama Store. The methods used in this project are interview, observation, and system simulation. The output of this project is a Microsoft Excel-based inventory management system which contains input of product lists, inventory journals, stock cards, remaining stock reports, and sales reports. After implementing this inventory management system has made it easier for the store to carry out operational activities and maintain a smooth operating cycle. Further projects are recommended to develop systems that support the operation of more resilient facilities.